2019
DOI: 10.1111/jan.14143
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of a mobile application‐assisted nurse‐led model used to improve treatment outcomes in children with asthma

Abstract: Aim To evaluate the effectiveness of a mobile application‐assisted nurse‐led management model in childhood asthma. Background Studies have shown that a nurse‐led asthma management model can improve asthma outcomes. However, the role of a mobile application‐assisted nurse‐led model in paediatric asthma management has not been studied well. Design A multi‐centre randomized clinical trial. Methods The trial was conducted between March 2017–March 2018. A total of 152 children (6 to 11.9 years old) were enrolled, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 28 publications
1
39
0
Order By: Relevance
“…The study was conducted to determine the effectiveness of participating in a school nurse-led asthma intervention on symptoms, asthma self-management with PFM usages, daily activities, and school absences. These study results were consistent with previous studies, which found that children who participated in asthma programs had fewer asthma symptoms (Fiks et al, 2015;Grover et al, 2016;Horner et al, 2016;Kintner et al, 2015;Lv et al, 2019;Payrovee et al, 2014;Rasberry et al, 2014;Suwannakeree et al, 2016), increased their knowledge and skills about asthma management (Fiks et al, 2015;Grover et al, 2016), used the PFM more often (Suwannakeeree et al, 2016), missed less school days (Fiks et al, 2015;Suwannakeeree et al, 2016), and they reported better quality of life (Grover et al, 2016). When children are accountable for their own health, they may feel more responsible and ready to manage their own health, which may lead to a smoother transition into puberty and adulthood.…”
Section: Discussionsupporting
confidence: 93%
“…The study was conducted to determine the effectiveness of participating in a school nurse-led asthma intervention on symptoms, asthma self-management with PFM usages, daily activities, and school absences. These study results were consistent with previous studies, which found that children who participated in asthma programs had fewer asthma symptoms (Fiks et al, 2015;Grover et al, 2016;Horner et al, 2016;Kintner et al, 2015;Lv et al, 2019;Payrovee et al, 2014;Rasberry et al, 2014;Suwannakeree et al, 2016), increased their knowledge and skills about asthma management (Fiks et al, 2015;Grover et al, 2016), used the PFM more often (Suwannakeeree et al, 2016), missed less school days (Fiks et al, 2015;Suwannakeeree et al, 2016), and they reported better quality of life (Grover et al, 2016). When children are accountable for their own health, they may feel more responsible and ready to manage their own health, which may lead to a smoother transition into puberty and adulthood.…”
Section: Discussionsupporting
confidence: 93%
“…Using smartphones may also assist in paediatric patient follow‐up. After consultation, the use of smartphones affords clinical information and online consultation with parents; one study showed that the infection rate and duration of antibiotic use could be reduced (Lv et al., 2019 ). Additionally, the automated message texting system combined with the hospital information system was used in pelvic inflammatory disease patient follow‐up; this method improved the short‐term clinical follow‐up and reduced the infection rate (Trent et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Managing patients with chronic comorbid diseases Two RCTs examined three indicators of successfully managing patients with complex chronic multimorbid health conditions in care homes, 43 and with asthma 53 showed no significant differences between CDSS users and non-users for emergency room usage, hospitalisation and complexity of medication regimens.…”
Section: Antenatal and Peripartum Carementioning
confidence: 99%